The Role Of Content Marketing Elements In Improving The Brand Image A Survey Study Of Syronex Brand Consumers In Lattakia Governorate - نصور, ريزان; وحود , نور; حماد, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aimed to study the role of content marketing in improving the mental image of the brand, by studying the role of content marketing elements (attractiveness, relevance, value) in improving the mental image. The researcher relied on the descriptive analytical method as a general approach to the research, where a questionnaire was designed and distributed to the research sample consisting of 318 individuals from the consumers of Seronex screens in Lattakia governorate (rural and city), and the researcher also used the statistical program spss to analyze the answers of the research sample. The researcher concluded that there is a positive, significant effect of content marketing on the mental image of Syronex, and the dimensions of content marketing were arranged in terms of this degree of influence in the following order: relevance, value, attractiveness.